ดอน กีโฆเต้ เด ลา มันช่า และอิทธิพลที่มีต่อบทละครเพลงอเมริกันเรื่อง แมน ออฟ ลา มันช่า และบทละครเพลงไทยเรื่อง สู่ฝันอันยิ่งใหญ่ - สุภัททิรา รอดบุญธรรม (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This thesis has two objectives: to study and analyze elements and contexts of Don Quijote de la Mancha, and to compare and contrast it with Man of la Mancha and Suu Fan An Ying Yai as the last two musical plays were influenced by Cervantes s text. The research shows that Don Quijote de la Mancha reflects the influence of its social and literary contexts in various parts. Moreover, as the text s aim was to satirize the chivalric novel, its plot, main character and theme were created especially for that purpose. At the same time, the actions and goals of the main character give us a picture of a man who tries to keep his goals among arising conflicts. This theme has influenced many later works. It is also found that although Man of la Mancha and Suu Fan An Ying Yai were influenced by Don Quijote de la Mancha interms of plot, characters and theme, each of these later works differs from the original text in its social context and author s aim and interpretation